2004
DOI: 10.1016/s1567-1356(03)00200-9
|View full text |Cite
|
Sign up to set email alerts
|

The yeast : a new host for heterologous protein production, secretion and for metabolic engineering applications

Abstract: Molecular tools for the production of heterologous proteins and metabolic engineering applications of the non-conventional yeast Zygosaccharomyces bailii were developed. The combination of Z. bailii's resistance to relatively high temperature, osmotic pressure and low pH values, with a high specific growth rate renders this yeast potentially interesting for exploitation for biotechnological purposes as well as for the understanding of the biological phenomena and mechanisms underlying the respective resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 53 publications
2
45
0
1
Order By: Relevance
“…The S. cerevisiae ALO1 and A. thaliana LGDH genes were also successfully expressed in Z. bailii (Table 2). Z. bailii was selected for this study because it tolerates high-sugar concentrations, acidic environments, and relatively high temperatures and can survive in the presence of high concentrations of chemical preservatives (3). Because of some of these features, fermentation bioprocesses could be performed at very low pH values, simplifying the downstream process and, at the same time, preventing bacterial contamination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The S. cerevisiae ALO1 and A. thaliana LGDH genes were also successfully expressed in Z. bailii (Table 2). Z. bailii was selected for this study because it tolerates high-sugar concentrations, acidic environments, and relatively high temperatures and can survive in the presence of high concentrations of chemical preservatives (3). Because of some of these features, fermentation bioprocesses could be performed at very low pH values, simplifying the downstream process and, at the same time, preventing bacterial contamination.…”
Section: Resultsmentioning
confidence: 99%
“…70191-4). Finally, the coding regions were cloned into the S. cerevisiae expression vectors of the pYX series (R&D Systems, Inc.) or the Z. bailii expression vectors pZ 3 and pAG26 in the following manner. AGD and ALO1 were subcloned into pYX042 (integrative; LEU2 auxotrophic marker and S. cerevisiae triose phosphate isomerase [TPI] promoter) with EcoRI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further improvements in lactic acid productivity were obtained by using S. cerevisiae strains lacking any pyruvate decarboxylase activity and thus unable to produce ethanol (15). Production of lactic acid was also attempted in nonconventional yeasts, e.g., Kluyveromyces lactis (2,17), Torulaspora delbrueckii (16), and Zygosaccharomyces bailii (4). Recently, it has been shown that the production of lactic acid in S. cerevisiae is strongly dependent on the genetic background of the host and on the source of the heterologous L-lactate dehydrogenase (5).…”
mentioning
confidence: 99%